Encounters along Micro-Level Borders: Silence and Metacommunicative Talk in Service Encounter Conversations between Finnish Employment Officials and Immigrants - Tarja Tanttu (Culture Unbound: Journal of Current Cultural Research, 2014)
This article examines the interaction between Finnish employment officials and their immigrant clients in service encounter conversations. It employs the concepts of metacommunicative talk, silence, agency and asymmetric interaction situation. Such service encounters between native speakers of Finnish and immigrants going through the integration process and speaking Finnish as their second language constitute situations of institutional interaction, characterised by asymmetry. Asymmetry during the service encounter arises from the roles and power relations between the official and client, a familiarity with the routines associated with service encounters, and the use of Finnish as the language of conversation during the encounter.